PENGEMBANGAN UMKM DENGAN ANALISIS LINGKUNGAN BISNIS KETERAMPILAN MANAJEMEN DAN PINJAMAN MODAL - Ibrahim Hafid (Jurnal Keuangan dan Perbankan, 2014)
The purpose of this study was to analyze and determine the influence of the business environment, managementskills, and capital loans to business potential, scale of operations and improved performance of SMEs.This research was conducted through a survey to a number of SME business units that had received loans fromrural banks with a number of samples and 220 respondents that were analyzed using structural equationmodeling (SEM). The results of this study indicated the potential effect on the business environment of business,business scale, but it did not affect the performance improvement. The management skill influencedbusiness potential, business scale and performance improvement. Capital loans affected potential business,business scale, and performance improvement. Business potential influenced performance improvement but itdid not affect the scale of business. Business Scale affected performance improvement efforts.